2022
DOI: 10.1186/s12862-022-02090-x
|View full text |Cite
|
Sign up to set email alerts
|

Host-plant adaptation as a driver of incipient speciation in the fall armyworm (Spodoptera frugiperda)

Abstract: Background Divergent selection on host-plants is one of the main evolutionary forces driving ecological speciation in phytophagous insects. The ecological speciation might be challenging in the presence of gene flow and assortative mating because the direction of divergence is not necessarily the same between ecological selection (through host-plant adaptation) and assortative mating. The fall armyworm (FAW), a major lepidopteran pest species, is composed of two sympatric strains, corn and rice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Our f-branch results also indicate gene flow between the two genetic clusters (Figure 4b), which aligns with the field conditions in the Americas (Dumas, 2015). Our phylogenetic results, along with previous studies, suggest that the rice strain may represent an earlier divergent population (Fiteni et al, 2022;Yainna et al, 2022). Previous studies have reported detection of rice-strain Tpi in the Eastern hemisphere based on a single site, TpiE-183 (Jing et al, 2020;Tay et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Our f-branch results also indicate gene flow between the two genetic clusters (Figure 4b), which aligns with the field conditions in the Americas (Dumas, 2015). Our phylogenetic results, along with previous studies, suggest that the rice strain may represent an earlier divergent population (Fiteni et al, 2022;Yainna et al, 2022). Previous studies have reported detection of rice-strain Tpi in the Eastern hemisphere based on a single site, TpiE-183 (Jing et al, 2020;Tay et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…2 B should be considered to be sfC, even though a proportion of this group was classified as sfR according to the mitochondrial COX1 marker because these samples were sampled only from corns. We reported that the TPI marker can be reliably used to identify host plant strains (sfC or sfR) whereas the COX1 marker should be used to identify two phylogenetic entities within sfC 48 . In this study, according to the TPI marker, almost all invasive FAWs were classified as sfC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotides with a Phred score less than 20 and adapter sequences were removed from the reads using AdapterRemoval v2.1.7 72 . Reads were mapped against the ver7 reference genome ( https://bipaa.genouest.org/sp/spodoptera_frugiperda_pub/download ) 48 , which had chromosome-sized scaffolds, using bowtie2 v2.3.4.1 with the -very-sensitive-local preset 73 . The read depth of mapping of resequencing data was 17.72X in the median.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations